Electric Charge transmission through Four Bosons - Chauca, J.; Doria, R.; Soares, I. (JOURNAL OF ADVANCES IN PHYSICS, 2017)
A non-Maxwellian model based on four bosons is considered. Based on an enlarged U(1)ï‚´SO(2) abeliansymmetry and preserving the postulates of light invariance and electric charge conservation its aim is to transfer electric charge ï„Q = 0 and | ï„Q|= 1 . For this, it enlarges Maxwell by associating a fields set , , ï‚± ï ï ï A U V . An electromagnetic system with four intermediary bosons is proposed. It introduces a new electric charge physics, a new electromagnetic transmission and a new photon physics. Thus, this work says that, while Maxwell electromagnetism focus on charge distribution and forces, there is still room for an electromagnetism based on charge transmission and gauge bosons. A new interpretation on the meaning of electric charge flux through gauge bosons is taken. Instead of just mediating different nature forces, the gauge bosons physics should be first understood as a mechanism for transferring energy-momentum and quantum numbers as electric charge. At this way, for electric charge transportation four connected gauge bosons are necessary. They are the photon, massive photon and two charged fields. For this, a whole quantum field theory supported on the set principle is generated. It is based on the fields family meaning associated to a same Lorentz representation (i, j) and tied up by a common gauge symmetry. Our physical case are four bosons from ) 21, 21 (representation sharing an abelian symmetry. This four set provides the physicity necessary for transmitting any electric charge value. A new perception for the electromagnetic phenomena is envisaged. It is generalized for a four fields abelian Lagrangian made of with antisymmetric and symmetric fields strengths, producing three and four abelian vertices, and generating whole relativistic equations with seven new features. It holds a dynamics carrying spin-1 and spin-0, based on granular and collective fields strengths, set determinism with directive and chance, quanta network, nonlinearity, neutral charges, photonics. A new scale for electromagnetic interaction is proposed. New intensities and range are derived through coupled nonlinear equations, massive particles and the presence of coupling constants beyond the electric charge. A light universality is obtained. Light becomes an absolute (light invariance), ubiquous (couplings constants diverse from electric charge), directive (fields set vector), contingencies producer (relativism and chance), inner light (selfinteracting photons).